EXPLORATORY RESEARCH FOR DEVELOPING ADVANCED PUMPING AND COMPRESSOR EQUIPMENT ADAPTED TO ABNORMAL OPERATING CONDITIONS OF OIL AND GAS PRODUCTION - Sazonov, Yuri; Mokhov, Mikhail; Mulenko, Vladimir; Tumanyan, Khoren; Frankov, Mikhail; Voronova, Victoria (Journal of Applied Engineering Science, 2020)
The observed instability of the oil and gas market makes it necessary to intensify the exploratory scientific research for the development of advanced and inexpensive pumping and compressor equipment intended for oil and gas production and treatment. The ongoing research work is being undertaken with a view to modernize well-known technical solutions and develop new scientific principles for gas compression with the use of labyrinth compressors. From the published materials it became known that when designing labyrinth pumps, the screw auger on the pump rotor can be replaced with a set of vane wheels. This design approach should be transferred from the field of pumping technology to the field of compressor technology as well. At the initial stage of such research microlevel models of new turbocompressors have been developed to test their performance. Further, was made the transition from the low-cost physical experiments with micro-level models to a deeper study of the working process for the basic model of the compressor with the screw rotor. 3D-model development was carried out with the use of the SolidWorks 3D CAD-system. In order to undertake a calculation study, the FloEFD software package of computational fluid dynamics developed by Mentor Graphics Corporation has been used. The results of the research findings can be used for the development of energy-efficient technologies for the compression and pumping of various gases. The development of cheaper and more economical pump-compressor units will allow for the solution of urgent hydrocarbon exploration and production problems in abnormal operating conditions. Based on similar compressor units, there is a possibility to develop other sectors of science and technology as well.